Análise faunística de gafanhotos (Orthoptera, Acridoidea: Acrididae, Romaleidae e Proscopiidae), no município de São Sepé, RS - Carvalho, Nathália Leal de (2010)
An average of 20,000 species of the Order Orthoptera are worldwide known and have great importance due to the economic damage caused by some species in agricultural areas. Thus, this study aimed to characterize the community of Acridoidea through biodiversity and faunal analysis in order to determine the optimum size of the sample as well as the ideal time of collection. Three experiments were conducted in the municipality of Sao Sepe, Brazil, one for each of the goals. Samples were collected between January and May 2009 in two areas of native grassland. With the purpose of catching insects, we used a data collection network, proposed by Costa and Carvalho, with which he toured different sample sizes (distance). The collected samples were placed in plastic bags and taken to the Laboratory of Entomology of the Federal University of Santa Maria for screening. They have afterwards been referred to the Laboratory of Entomology of the Bioscience faculty of PUC, Brazil, and identified by Professor Maria Katia Matiotti Costa to the taxonomic category of species. 2913 copies were collected, distributed into 22 (twenty two) species, belonging to 17 (seventeen) genera, and three (3) families as it follows: Acrididae, and Proscopiidae Romaleidae. The species Scotussa cliens (Stål, 1860), Dichroplus silveiraguidoi Liebermann, 1956 and Notopomala glaucipes (Rehn, 1905), were classified as dominant, common, and abundant. All species showed accidental constancy. The sampling method developed by Costa and Carvalho was efficient. The optimum size of the sample was 25m as it showed the largest number of specimens and species diversity. The best time of collection was by 1:30 p.m., where the greatest number of samples and species diversity has been collected.